Establishing the bleeding and diffusion of chromophores from lining/upper fabrics in shoes to MidSole in sneakers – a case study - Seah, Dean G. J. (2024)
‘Chemical’ migration, in particular bleeding, in the footwear industry is an issue that has not been well understood. In this work, a specific case problem is investigated concerning the occurrence of black-colored staining in the polyurethane (PU) midsole after production of the shoes and storage in a warehouse for about 4–6 wk. Considering the qualitative nature of the standard tests employed in the footwear industry (like SATRA TM340 and TM 343), here, (chemical) methodologies are designed to understand and identify the source of chromophore(s), how they are transferred to PU, and their diffusion kinetics. In this process, different chosen temperatures and relative humidity conditions are employed to evaluate their influence on the transfer and diffusion of chromophores from the lining/upper fabrics. Preparative chromatography and high-resolution mass spectroscopy have enabled the identification of the responsible chromophores for the coloration of the shoe sole. This work provides a fundamental base for understanding a significant issue in the footwear industry.